2020
DOI: 10.3390/tropicalmed5030134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Systems on the Implementation of Intermittent Preventive Treatment for Malaria in Pregnancy in Sub-Saharan Africa: A Narrative Synthesis

Abstract: Malaria in pregnancy is a public health challenge with serious negative maternal and newborn consequences. Intermittent preventive treatment (IPTp) with sulphadoxine-pyrimethamine is recommended for the control of malaria during pregnancy within endemic areas, but coverage for the recommended ≥3 doses IPTp regimen has remained suboptimal. We searched PubMed, Cochrane library, and HINARI database from 1 January 2010 to 23 May 2020, for studies investigating the effect of the health system on IPTp implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…In addition, failure to provide women with information on the benefits of MiP interventions, shortage of health staff, resulting in high patient load and failure to offer women SP due to complaints of side effects affected uptake of MiP interventions and were reported in some of the analysed studies. Other studies have equally reported that health system barriers such as stockouts and user fees impacted negatively on women’s access to IPTp-SP and LLIN in sub-Saharan Africa [ 28 , 33 , 34 , 36 , 72 ]. Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, failure to provide women with information on the benefits of MiP interventions, shortage of health staff, resulting in high patient load and failure to offer women SP due to complaints of side effects affected uptake of MiP interventions and were reported in some of the analysed studies. Other studies have equally reported that health system barriers such as stockouts and user fees impacted negatively on women’s access to IPTp-SP and LLIN in sub-Saharan Africa [ 28 , 33 , 34 , 36 , 72 ]. Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, failure to provide women with information on bene ts of MiP interventions, shortage of health staff resulting in high patient load and failure to offer women SP due to complaints of side effects affected uptake of MiP interventions and were reported in some of the analysed studies. Other studies have equally reported that health system barriers such as stockouts and user fees impacted negatively on women's access to IPTp-SP and LLIN in sub-Saharan Africa [28, 33,34,36,71]. Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [72].…”
Section: Discussionmentioning
confidence: 99%
“…Use of the PTRC analysis tool provided the MAPD team with systematic insights into the barriers effecting program implementation and possible solutions to address them to close the e cacy-effectiveness gap for IPTp [22]. Use of the PTRC analysis tool identi ed similar barriers in a narrative synthesis by Olaleye and Walker (2020), which found that factors effecting the supply and demand for IPTp services involve all pillars of the health system across sub-Saharan Africa [23].…”
Section: Improved Sp Supply Chain Managementmentioning
confidence: 99%
“…Evidence from systematic reviews and meta-analysis of studies conducted in sub-Saharan Africa identi es the inconsistent provision of IPTp and ITNs services compounded by unclear policy and guidance on IPTp as key barriers to the control of MIP [4][5][6][7][8][9][10][11][12]. Other factors that contribute to the problem include weak healthcare systems, frequent stock-outs of essential medicines and commodities, high user fees, and sub-optimal quality of services [10,13].…”
Section: Introductionmentioning
confidence: 99%